(untitled) (Encuentros, 2021)
This review article analyzes research trends on the contributions of products and practices artistic in the construction of memories on tragic experiences of the recent past. According to the collaborative nature of these initiatives, by including survivors/victims and communities as co-creators, the analysis evidences the emphasis on visual language in the processes of creation, distribution and reception of this type of artistic content. The review was based on tools of grounded theory and uses coding and interpretation dates matrices. Finally, the article exposes three conclusions: the emergence of diverse artistic-aesthetic ventures; the emergence of new relationships between artists and victims/survivors; and the dilemmas around the possible trivialization or reflection on these facts in the hearings, after the massification of these visual representations in the public sphere.